Respiratory symptoms in relation to residential coal burning and environmental tobacco smoke among early adolescents in Wuhan, China: a cross-sectional study - Liu Chunhong; Avol Edward L; Kissling Grace E; Li Yan; Johnson C Anderson; Xia Jiang; Salo Päivi M; London Stephanie J (BMC, 2004)
Abstract Background Cigarette smoking and coal burning are the primary sources of indoor air pollution in Chinese households. However, effects of these exposures on Chinese children's respiratory health are not well characterized. Methods Seventh grade students (N = 5051) from 22 randomly selected schools in the greater metropolitan area of Wuhan, China, completed an in-class self-administered questionnaire on their respiratory health and home environment. Results Coal burning for cooking and/or heating increased odds of wheezing with colds [odds ratio (OR) = 1.57, 95% confidence interval (CI): 1.07-2.29] and without colds (OR = 1.44, 95% CI: 1.05-1.97). For smoking in the home, the strongest associations were seen for cough (OR = 1.74, 95% CI: 1.17-2.60) and phlegm production (OR = 2.25, 95% CI: 1.36-3.72) without colds among children who lived with two or more smokers. Conclusions Chinese children living with smokers or in coal-burning homes are at increased risk for respiratory impairment. While economic development in China may decrease coal burning by providing cleaner fuels for household energy use, the increasing prevalence of cigarette smoking is a growing public health concern due to its effects on children. Adverse effects of tobacco smoke exposure were seen despite the low rates of maternal smoking (3.6%) in this population.